1993
DOI: 10.1111/j.1476-5381.1993.tb13760.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of α‐adrenoceptor agonists on intracellular Ca2+ levels in freshly dispersed single smooth muscle cells from rat tail artery

Abstract: 1 The presence of functional x-adrenoceptors in freshly dispersed single smooth muscle cells from rat tail arteries was investigated by use of selective ax-adrenoceptor agonists and antagonists. 2 Cirazoline, a selective a,-adrenoceptor agonist, caused a prazosin-sensitive, rapid but transient increase in intracellular Ca2 , which was partially inhibited by the voltage-dependent Ca2+ channel blocker, nifedipine. 3 TL99, an a2-adrenoceptor agonist, in the presence of prazosin, initiated a slow and sustained inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
2

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
6
2
Order By: Relevance
“…Our results support this hypothesis; in the Ca 2 +-free medium Epi still increased [Ca 2 +]i, and this increase was highly sensitive to yohimbine and WB 4101 but was resistant to prazosin. Our findings are distinct from those in reports on myocytes isolated from rat tail artery [26] and rat portal vein [7], in which the increase in [Ca2+]i by activation of a 2 -ARs was solely from the Ca 2 entry through VDCCs. These discrepancies may be due to the difference in preparations, because the rat myocytes contain both at-ARs and O 2 -ARs, with a-ARs outnumbering at 2 -ARs [27,28], whereas porcine myometrial cells contain predominantly a 2 -ARs with few al-ARs [2].…”
Section: Discussioncontrasting
confidence: 84%
“…Our results support this hypothesis; in the Ca 2 +-free medium Epi still increased [Ca 2 +]i, and this increase was highly sensitive to yohimbine and WB 4101 but was resistant to prazosin. Our findings are distinct from those in reports on myocytes isolated from rat tail artery [26] and rat portal vein [7], in which the increase in [Ca2+]i by activation of a 2 -ARs was solely from the Ca 2 entry through VDCCs. These discrepancies may be due to the difference in preparations, because the rat myocytes contain both at-ARs and O 2 -ARs, with a-ARs outnumbering at 2 -ARs [27,28], whereas porcine myometrial cells contain predominantly a 2 -ARs with few al-ARs [2].…”
Section: Discussioncontrasting
confidence: 84%
“…Radioligand binding assays with membranes from rat tail arteries (Gheung and Triggle 1988), isolated tissue preparations (Abe et al 19871, and freshly dispersed single vascular smooth muscle cells (Li et al 1993) have demonstrated that both aa-and a2-a&enoceptors are present on the postsynaptic cell membrane. In the present study, a differential sensitivity to PTX versus CTX was demonstrated, suggesting that at least one PTX-sensitive G-protein is involved in the regulation of a-adrenoeeptor-mediated vasoconstriction.…”
Section: Discussionmentioning
confidence: 98%
“…To address this questionS we have (i) investigated almd a2-adrenoceptor agonist stimulated contractile responses of rat tail artery rings from rats that were hypertensive (SHR) or nomotensive (WKY and Sprague -Dawley (SD)) and determined the effects of a-adrenocepterr antagonists and nifedipine on the responses to these agonists, and (ii) compared the effects of in vivs pretreatment with PTX or CTX on the contractile responses induced by al-and a2-adrenoceptor agonists in tail artery rings from these three strains of rats. The rat tail artery has the advantage that in comparison to most other arterial vessels, studies with radioligand binding assays (Cheung and Triggle 1988) and isolated tissue preparations (Abe et al 1987), as well as freshly dispersed single vascular smooth muscle cels (Li et al 1993), have demonstrated that postsynaptic al-and a2-adrensceptors are present in this tissue.…”
mentioning
confidence: 98%
“…Stimulation of al-adrenoceptors in rat aorta activates extracellular Ca2" influx and/or intracellular Ca2+ release for contraction (Cauvin & Malik, 1984). In rat tail artery al-adrenoceptors mediate a fast and transient increase in intracellular Ca2+ which is probably the result of the mobilization of intracellular calcium and Ca2" influx through receptor-operated channels (Li et al, 1993). In addition, direct studies in tail artery rings using Fura 2 (Thorin & Atkinson, 1994) or indirect studies using inositol phosphate accumulation (Labelle & Murray, 1990;Vila et al, 1993) (Chiu et al, 1987).…”
Section: Discussionmentioning
confidence: 99%